Dry-spinning of cellulose nanocrystal/polylactic acid composite fibers. Issue 1 (29th January 2018) - Clarkson, Caitlyn M; Youngblood, Jeffrey P
Abstract : In the present study, the authors explored the viability of dry-spinning to produce cellulose nanocrystal (CNC) and polylactic acid composite fibers from dimethylformamide solutions. Fiber surface morphology, crystallinity and mechanical properties were assessed for fibers with 0, 1, 3 and 5 wt% CNCs. The fiber morphology transitioned from smooth to sharkskin to severe melt fracture with increasing extrusion speed. Surface morphology appeared to be weakly dependent on CNC content and addition of CNCs did not reduce melt fracture. Addition of 1 wt% CNC resulted in the highest crystallinity, an approximately 30% increase for the dry-spun composite fibers. Fibers exhibited a mixture of ductile and brittle-like behavior during mechanical testing. The elastic modulus and strength at failure were measured for three fiber diameter ranges and for increasing CNC content. A maximum average elastic modulus of 6·5 GPa and 100 MPa increase in strength at failure are reported for dry-spun composite fibers.